B Part of It School Leaver protocol: an observational repeat cross-sectional study to assess the impact of a meningococcal serogroup B (4CMenB) vaccine programme on carriage of Neisseria meningitidis. Issue 5 (6th May 2019) - Marshall, Helen S; McMillan, Mark; Koehler, Ann; Lawrence, Andrew; MacLennan, Jenny; Maiden, Martin; Ramsay, Mary; Ladhani, Shamez N; Trotter, Caroline; Borrow, Ray; Finn, Adam; Sullivan, Thomas; et al.
Abstract : Introduction: Invasive meningococcal disease is uncommon but associated with a high-case fatality rate. Carriage prevalence of the causative bacteria, Neisseria meningitidis, is high in adolescents. A large (n=34 500) cluster randomised controlled trial (RCT) to assess the impact of a meningococcal B (MenB) vaccine on meningococcal carriage was implemented in the state of South Australia (SA) for year 10, 11 and 12 senior school students in 2017–2018. This study will assess the impact of MenB vaccine (4CMenB) on carriage prevalence in school leavers in SA, 1 and 2 years after implementation of the cluster RCT in adolescents. Measuring the impact of population programmes on carriage can assist in informing future meningococcal immunisation programmes such as targeted age groups and use of catch-up campaigns. Methods and analysis: This repeat cross-sectional study will assess carriage prevalence in 2018 and 2019. All school leavers who attended year 12 in any school in SA in 2018 or 2019 will be invited to participate in this study. An oropharyngeal swab will be taken from each participating student and a risk factor questionnaire completed by the student following informed consent. Students will attend clinics at SA universities, technical colleges, and metropolitan, rural and remote government council clinics. Confirmed vaccination history will allow a comparison in carriage prevalence between vaccinated and unvaccinated school leavers. A sample size of 4096 students per year will provide 80% power to detect a 20% difference in carriage prevalence of disease-causing meningococci (defined as genogroup A, B, C, W, X or Y) between years. Ethics and dissemination: The study was approved by the Women's and Children's Health Network Human Research Ethics Committee. Results will be published in international peer review journals and presented at national and international conferences. Trial registration number: NCT03419533 ; Pre-results